Effects of Inbound Tourism on the Ecological Footprint. An Application of an Innovative Dynamic Panel Threshold Model - Xiaojuan Li (Frontiers in Environmental Science, 2022)
This study uses a new and innovative dynamic panel threshold technique to examine the relationship between inbound tourism and ecological footprint (EF). This method was applied to the 10 most popular destinations spanning 1995–2021. These findings demonstrate that inbound tourism and EF have a threshold effect. To be specific, we find that only a certain threshold of tourism is beneficial to the environment; beyond that point, increasing tourism is likely to cause EF. Additionally, economic growth, infrastructure investment, and energy all benefited the EF. But water availability negatively affects EF. The findings of this study may have important policy implications for policymakers.